2016
DOI: 10.3892/or.2016.5010
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-106a regulates phosphatase and tensin homologue expression and promotes the proliferation and invasion of ovarian cancer cells

Abstract: Abstract. Ovarian cancer is a leading cause of malignant gynecological tumor-related mortality among women. The treatment of ovarian cancer patients continues to be challenging. MicroRNA-106a (miR-106a) is widely expressed in diverse human tumors. In the present study, we investigated the biological and pathological roles of miR-106a in ovarian cancers. We found that miR-106a expression was significantly increased in primary ovarian cancer tissues and ovarian cancer cells compared with the level in normal tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…and amplified region, and are implicated in tumorigenesis and tumor development (11). miRNAs are also involved in modulating different cancer-related biological processes, such as cell proliferation, cycle, apoptosis, angiogenesis, invasion, migration and metastasis (12)(13)(14). Moreover, numerous miRNAs are aberrantly expressed in various kinds of human cancers, such as EOC (15), cervical cancer (16), gastric cancer (17), lung cancer (18) and bladder cancer (19).…”
Section: Microrna-455 Inhibits Cell Proliferation and Invasion Of Epimentioning
confidence: 99%
“…and amplified region, and are implicated in tumorigenesis and tumor development (11). miRNAs are also involved in modulating different cancer-related biological processes, such as cell proliferation, cycle, apoptosis, angiogenesis, invasion, migration and metastasis (12)(13)(14). Moreover, numerous miRNAs are aberrantly expressed in various kinds of human cancers, such as EOC (15), cervical cancer (16), gastric cancer (17), lung cancer (18) and bladder cancer (19).…”
Section: Microrna-455 Inhibits Cell Proliferation and Invasion Of Epimentioning
confidence: 99%
“…Emerging data have demonstrated that the abnormal expression of miRNAs contributes to a number of diverse biological and pathological processes in cancer cells, including in cell proliferation, cell cycle, differentiation, development, apoptosis, migration, invasion and metastasis (12)(13)(14). Previous studies have revealed that miRNAs are involved in the carcinogenesis and progression of several types of human cancer as either oncogenes or tumor suppressors, depending on the functions of their target mRNAs (15)(16)(17). The inactivation of oncogenic miRNAs, or restoration of tumor suppressing miRNAs, has demonstrated potential in providing therapeutic treatments for patients with cancer, and the strategies are undergoing clinical trials (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, miR-106a, which is derived from the precursor miR-106a-363 on chromosome Xq26.2, was revealed to play a critical role in the progression of cancers (13)(14)(15)(16)(17). A previous study revealed that miR-106a functions as a regulator of cell invasion, proliferation and drug sensitivity (18). miR-106a functioned as an oncogene in human gastric cancer and contributed to proliferation and metastasis in vitro and in vivo and a high expression of miR-106a was associated with the poor survival rate of gastric cancer patients (19,20).…”
Section: Introductionmentioning
confidence: 99%